Prediction of Ultimate Antifloating Force of Bored Piles in Urban Road Crossing Overpass - Minxia, Zhang; Kaijun, Fan; Shengrong, Liao; Ping, Xu; Jinwei, Li; Chen, Chen (Geofluids, 2022)
As an effective antifloating measurement in underpass engineering, uplift piles have been widely employed in the antifloating design of underground structures, such as basements, underground roads, and underground shopping malls. For the purpose of studying the antifloating behavior of bored piles and predicting the uplift bearing capacity in underpass engineering, the on-site pull-out tests of bored piles are carried out in laboratory. Besides, the MMF growth curve model, the ordinary hyperbolic model, and the exponential model are employed to fit and predict the ultimate bearing capacity of the measured uplift load and uplift displacement data of three test piles, respectively. The research results indicate that three test piles meet the stability requirements of antibuoyant bearing capacity, and the pull-up load-displacement curves of test piles are gentle and steep. Meanwhile, the fitting accuracy of the pull-displacement curve is high; specifically, the correlation coefficient is above 0.98619, and the average value is 0.99134, thereby verifying that the fitting effect of MMF growth curve model is better than those of the hyperbolic model and the exponential model. Therefore, the MMF growth curve model proposed in this paper not only describes the fitting of the uplift load-uplift displacement curve of uplift piles accurately but also predicts the ultimate bearing capacity of test piles. The research results provide an important reference for the antifloating behavior of bored piles in underpass engineering.